Evidence for a JAK2/STAT3 proinflammatory and vasculogenic mimicry interrelated molecular signature in adipocyte-derived mesenchymal stromal/stem cells - Carolane Veilleux; Marie-Ève Roy; Alain Zgheib; Michel Desjarlais; Borhane Annabi (Cell Communication and Signaling)
Abstract Background During obesity, the excessive accumulation of fat in tissue promotes dysregulated hormonal and cytokine homeostasis that triggers chronic inflammation, which is, in part, associated with an increased incidence of some cancers. This protumoral inflammatory environment is further exacerbated through the secretome of mature adipocytes, which promotes tumor angiogenesis. Emerging studies suggest that human adipocyte-derived mesenchymal stromal/stem cells (ADMSCs) may contribute to a complementary process supporting local angiogenesis termed vasculogenic mimicry (VM). The molecular mechanisms linking ADMSCs to VM and inflammation remain poorly understood. Methods ADMSC 3D capillary-like structures were generated upon seeding on Cultrex. Structure analysis was performed using WIMASIS. Total RNA was extracted using TRIzol and RT-qPCR was performed to assess gene expression or screen RT2 PCR arrays. Transient gene silencing was performed by transfecting cells with a specific siRNA against STAT3. Protein lysates were harvested and used for Western blotting. Realtime cell migration was performed with the xCELLigence system. Results Our findings revealed that in vitro priming of ADMSCs with Cultrex led to the formation of 3D capillary-like structures and the acquisition of an inflammatory molecular signature. VM-derived ADMSCs share a common proinflammatory molecular signature similar to that induced in 2D ADMSC monolayers by tumor necrosis factor (TNF)-alpha and are characterized by upregulated expression of COX2, CCL2, CCL5, CXCL5, CXCL8, IL-6, SNAI1, and MMP9. Interestingly, pharmacological inhibition or gene silencing of the JAK2/STAT3 signaling pathway reduced chemotactic cell migration, in vitro VM and the expression of proinflammatory and invasive biomarkers. Conclusions Overall, we provide novel evidence that inhibiting JAK2/STAT3-regulated VM can also alter the acquisition of a proinflammatory signature and prevent the contribution of ADMSCs to alternative tumor neovascularization processes.